Design and Implementation of Inventory Domain for Enterprise Resource Planning Using SOA and Workflow Approach - Sunaryono, Dwi; Ahmadiyah, Adhatus Solichah; Sarno, Riyanarto; Setiaputra G, Riswandy (IPTEK Journal of Proceedings Series, 2014)
Enterprise resource planning (ERP) is a business management system which integrates several domains of enterprise business processes. Among several ERP domains, inventory is one of the basic requirement domains of an enterprise. Inventory holds three important functionalities, i.e., stock request, delivery, and stock control. In this paper, we have designed inventory domain using Service-oriented Architecture (SOA) to accommodate data communication between inventory domain and other ERP domains by providing services and employed Workflow approach to automate business process in inventory domain. The implementation confirms that our design has successfully accommodated the business processes in inventory domain. In term of technology, Workflow approach is beneficial to develop inventory domain application which is responsive to sub business process changes. In addition, the usage of SOA makes the developed inventory domain application is capable to provide services to be consumed by the other ERP domains.